Association of Human Papillomavirus Infection and Abnormal Anal Cytology among HIV-Infected MSM in Beijing, China - Yang, Yu; Li, Xiangwei; Zhang, Zhihui; Qian, Han-Zhu; Ruan, Yuhua; Zhou, Feng; Gao, Cong; Li, Mufei; Jin, Qi; Gao, Lei (PLOS ONE, 2012)
Background In the recent years, dramatic increases in HIV transmission among men who have sex with men (MSM) have been observed in China. Human papillomavirus (HPV) infection related anal cancer is more common among HIV-infected MSM as compared to the general population. However, HPV infection and anal cytology has been rarely studied in HIV-infected MSM in China. Methods HIV-infected MSM in Beijing, China were invited to participate in this study between January and April 2011. Anal swabs were collected for examining cytology and HPV genotypes. Results Ninety-five eligible participants with complete questionnaire and laboratory data were included in the analyses. Thirty six of them (37.9%) showed abnormal anal cytology as follows: atypical squamous cells of undetermined significance (ASC-US) in 19 (20.0%), atypical squamous cells but cannot exclude HSIL (ASC-H) in 1 (1.1%), low-grade squamous intraepithelial lesion (LSIL) in 15 (15.8%), and high-grade squamous intraepithelial lesion (HSIL) in 1 (1.1%). HPV6 (20.0%), HPV16 (10.9%), HPV56 (10.9%), HPV52 (9.1%) and HPV39 (9.1%) were observed most frequently among those with normal anal cytology, while different distribution was found in the ones with abnormal anal cytology as HPV6 (19.4%), HPV16 (19.4%), HPV45 (16.7%), HPV52 (16.7%) and HPV18 (11.1%). In addition, HPV16, HPV45, HPV52 and HPV18 were the most frequent high-risk types in patients with abnormal anal cytology. HPV multiplicity was found to be significantly related to the prevalence of abnormal anal cytology (p for trend = 0.04). Conclusions High prevalence of HPV infection and abnormal anal cytology was observed among HIV-infected MSM in China. Infection of multiple HPV types or high-risk types was found to be associated with an increased risk of abnormal anal cytology.